2021
DOI: 10.3390/ijerph182111111
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Practices of General Practitioners towards Oral Cancer and Emerging Risk Factors among Indian Immigrants in Australia: A Qualitative Study

Abstract: Background: In Australia, Indian immigrants are one of the fastest-growing communities. Since oral cancer is widespread in India, the indulgence of Indians in customs of areca (betel) nut use in Australia may be linked to the recent rise in oral cancer cases. Since GPs (general practitioners) are primary healthcare providers, it is pivotal to ensure the oral cancer awareness of GPs. This study aimed to explore oral cancer risk-related knowledge, beliefs, and clinical practices of GPs in Australia. Methods: Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A number of respondents also questioned the competency of GPs to advise them on oral cancer. These findings are not unforeseen as a recent qualitative study involving GPs in Australia raised similar concerns regarding their limited knowledge around new oral cancer risk factors, inconsistent clinical practices relating to routine oral cancer check-ups and referrals [ 37 ]. These views were supported by the findings of a review that explored the knowledge, attitudes and practices of general practitioners in developed countries regarding oral cancer [ 47 ].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A number of respondents also questioned the competency of GPs to advise them on oral cancer. These findings are not unforeseen as a recent qualitative study involving GPs in Australia raised similar concerns regarding their limited knowledge around new oral cancer risk factors, inconsistent clinical practices relating to routine oral cancer check-ups and referrals [ 37 ]. These views were supported by the findings of a review that explored the knowledge, attitudes and practices of general practitioners in developed countries regarding oral cancer [ 47 ].…”
Section: Discussionmentioning
confidence: 98%
“…The study questionnaire was initially developed using existing survey items identified from a comprehensive literature review [ 17 , 47 ] as well as preliminary exploratory work around oral cancer in Australia [ 31 , 37 ]. The questionnaire development was informed by the KAB model and Health belief model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oceania has always maintained a high level of OC incidence. Due to the geographical proximity of Oceania and South Asia, developed countries like Australia have more immigrants from South Asia, and studies have shown that their knowledge about OC is at a relatively low level 41,42 . In addition, the HPV infection rate of indigenous people in Oceania far exceeds the international average levels, which is also one of the reasons for the high incidence of OCs 43 .…”
Section: Discussionmentioning
confidence: 99%